Diphenyltetrazole Modified Bacterial Cellulose Film: Considerations on Heterogeneous Modification and Bioconjugation - Birkheur,Simone (2020)
Abstract Understanding chemical reactions in bacterial cellulose (BC) films is important to control the insertion of biomolecules that can improve their biomedical properties. Diphenyltetrazole molecules are able to react with tiols under UV irradiation and has been useful for immobilize proteins on different materials. In this work, we show the functionalization of a BC film with diphenyltetrazole and subsequent attempts of conjugation of the bovine serum albumin (BSA) to it. Diphenyltetrazole was synthesized in two steps, and functionalization of it with BC was carried out under ultrasound irradiation. Spectroscopic analysis of the film by UV–Vis and FTIR confirmed the success of the reaction. Attempts to conjugate BSA to the modified cellulose film by photoclick reaction failed under these conditions. Although this methodology is important in the conjugation of biomolecules, we understand that its application in cellulosic materials in heterogeneous phase is disadvantaged due to the half-life of the unstable intermediate and the biomolecule's access to it.